Intervensi Fisioterapi pada Kasus Sprain Ankle : A Case Report - Angger Perdana Wibowo; Isnaini Herawati; Warih Sri Widodo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Background: An ankle sprain is an acute musculoskeletal injury that causes damage to one or more ligaments in the ankle. There are 3 grades of damage to an ankle sprain, namely grade 1: mild ligament tear, grade 2: partial ligament tear, grade 3 : complete ligament tear. Therefore, this study aims to find out how to treat physiotherapy in cases of ankle sprains and the progress that patients find after being given intervention. Methods: This case study was carried out at Panembahan Senopati Hospital Bantul on ankle sprain patients. The problems experienced by patients are pain, weakness of muscle strength, limited range of motion of joints, and decreased functional activity. Findings: Numeric Rating Scale (NRS) pain assessment revealed that quiet pain remained at zero while pressure pain decreased from two to one and movement pain decreased from four to two. Ankle eversion, dorsiflexion, plantar flexion, and inversion are used in Manual Muscle Testing (MMT) to test muscle strength, and the results range from 3 to 4. Goniometers are used to measure range of motion (ROM) when moving plantar-dorso flexi S : 15 °-0-30° becomes S: 18°-0-32°, while in the inversion-eversion movement R: 25°-0-15° becomes R: 27°-0-17°. Functional activity as measured by the Foot and Ankle Disability Index (FADI) showed an increase, initially with a value of 71 which increased to 78. Conclusion: Providing intervention for ankle sprains with 3 meetings where the modalities used were infrared, active resisted exercise and calf raises were able to reduce pain relief, increasing muscle strength, increasing joint range of motion and functional activities